LD50 and LC50 Values of Ethanol Extracts From Herbs of Ketumpangan Air (Peperomia pellucida (L.) Kunth) - INDAH DWIATMI DEWIJANTI; MARISSA ANGELINA; SRI HARTATI; BETTY ERNAWATI DEWI; LIA MEILAWATI (Fakultas Farmasi Universitas Pancasila, 2014)
Ketumpangan air (Peperomia pellucida (L.) Kunth), an Indonesian wild plant, is commonly found in every Indonesian region with moist shady place. People usually consume ketumpangan air as a fresh vegetables. Empirically, ketumpangan air is consumed to treat fever, stomach disease, kidney disorders, drug abscesses, boils acne, headaches, pain in arthritic and rheumatic gout, or other external treatment. In this research, we tested the acute toxicity of ethanol extract from ketumpangan air using experimental animals mice DDY strain. We also tested the Brine Shrimp Lethality Test (BSLT) using Artemia salina Leach larva shrimp. The main aim of this reseach was to determine the LD50 and LC50 values of ethanol extract from Ketumpangan air. The results showed that the ethanol extract was categorized as ‘mild toxic’. The calculation of LD50 with Reed and Munich method showed that the LD50 value for male and female group was 15.13 g/ kg and 11.87 g/kg respectively. The BSLT result showed that the LC50 values of Ketumpangan air was 81.28 ppm.